Pengaruh Intensitas Menonton Tayangan Sinetron Anak Jalan Pada Perilaku Imitasi Siswa SMP (Jurnal Kajian Media, 2017)
In the current era of information globalization, Indonesia is enlivened by the presence of several private television stations such as ANTV, INDOSIAR, TRANSTV, MNC TV, RCTI, SCTV, GLOBAL TV, TV ONE, TRANS 7, METRO TV. All of these private televisions are trying to attract as many viewers as possible and can occupy the highest portion. Street children's soap operas that aired on RCTI succeeded in sucking the public's attention, not least the citizens of Surabaya. That's why television is very big influence in changing the behavior of the audience. Imitation is the first level of apparent influence, in which viewers see repeatedly the behavior of their idol figures and tend to mimic those behaviors. This is understandable because one of the developmental behaviors of a person is generated from their more mature examples, parents, family, teachers, even other people who become idols. They often witnessed the soap opera starring Stefan William and Nathasa Wilona whose name is now starting to stick out. The emergence of imitation behavior in adolescents is not "solely caused by television, but also related to the role of the family. Based on the above mentioned background, the purpose of the research is to know the relationship of Intensity watching Impressions of Street Children Sinetron Against Imitation Behavior at Junior High School Students of 24th Grade VIII Surabaya. This study uses descriptive quantitative, this study the authors use survey research methods. This research is classified in explanative type of research, the sample is 150 students, total sampling technique. Analytical techniques used using multiple linear regression, t test and correlation.Keywords: watch intensity, and imitation behavior